2021
DOI: 10.1371/journal.pone.0258110
|View full text |Cite
|
Sign up to set email alerts
|

Future-relevant memories are not selectively strengthened during sleep

Abstract: Overnight consolidation processes are thought to operate in a selective manner, such that important (i.e. future-relevant) memories are strengthened ahead of irrelevant information. Using an online protocol, we sought to replicate the seminal finding that the memory benefits of sleep are enhanced when people expect a future test [Wilhelm et al., 2011]. Participants memorised verbal paired associates to a criterion of 60 percent (Experiment 1) or 40 percent correct (Experiment 2) before a 12-hour delay containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 52 publications
(93 reference statements)
7
26
0
Order By: Relevance
“…Previous studies have demonstrated that overnight consolidation effects are strongest for information learned within a few hours of sleep [10,[46][47][48]. Our findings build on this prior…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Previous studies have demonstrated that overnight consolidation effects are strongest for information learned within a few hours of sleep [10,[46][47][48]. Our findings build on this prior…”
Section: Discussionsupporting
confidence: 85%
“…Memory retention is improved by post-learning sleep [5][6][7][8][9][10][11], suggesting that sleep supports the consolidation of newly learned information. Contemporary models of sleep-associated memory processing propose that memories are reactivated during sleep, and thereby integrated into long-term storage [5,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that sleep (vs wakefulness) supports memory consolidation (Gais et al, 2006;Ashton et al, 2020;Payne et al, 2012;Talamini et al, 2008;Gaskell et al, 2018;Cairney et al, 2018a;Durrant et al, 2016;Ashton & Cairney, 2021) and subsequent learning (Cousins et al, 2018;Kaida et al, 2015;McDermott et al, 2003;Saletin et al, 2016;Tempesta et al, 2016;Yoo et al, 2007). Consistent with these studies, we found that memory retention and next-day learning were better after overnight sleep than wakefulness.…”
Section: Sleep Benefits Overnight Consolidation and Next-day Learningsupporting
confidence: 90%
“…Sleep provides a benefit over wake for retaining memories and also for learning new ones (Gais et al, 2006;Ashton et al, 2020;Payne et al, 2012;Talamini et al, 2008;Gaskell et al, 2018;Cairney et al, 2018a;Durrant et al, 2016;Ashton & Cairney, 2021;Yoo et al, 2007;Tempesta et al, 2016;Alberca-Reina et al, 2014;Kaida et al, 2015;Cousins et al, 2018). Some suggest that these benefits can be explained by an active role of sleep, in particular, slow oscillation activity (SOA), in shifting memory dependency from hippocampus to neocortex, and thus increasing hippocampal capacity for new learning (Born & Wilhelm, 2012;Rasch & Born, 2013;Klinzing et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, two recent online studies using the same sleep manipulation as in the current study (Ashton & Cairney, 2021;Mak et al, in preparation) found clear evidence of a sleep benefit in the classic paired-associate learning paradigm, replicating well-established evidence from lab-based studies (e.g., Lo et al, 2014;Plihal & Born, 1997). Together, these suggest that it is possible to detect sleep-related memory effects in online experiments, as long as pre-registered exclusionary criteria and attention checks are put in place, both of which were implemented in the current (and the next) experiment.…”
Section: Methodsmentioning
confidence: 98%